Pengaruh Substitusi Sandblasting Pada Campuran Beton Mutu Tinggi - Roi Marthen; Jonie Tanijaya; Lisa Febriani (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
High quality concrete is a type of concrete that has been given special treatment, if no special materials are added, it cannot always be obtained with conventional materials. The purpose of this study was to determine the best sandblasting substitution composition in producing high quality concrete. The method used in the design of the mixture is the SNI method, with the design concrete quality of 42 MPa. The results of this study indicate that for testing the compressive strength of concrete at the age of 28 days, the highest value for the 10% sandblasting variation is 49,163 MPa, the split tensile strength of the 10% sandblasted concrete variation is 4.789. MPa, the flexural strength of 10% sandblasted concrete is 6,399 MPa and the modulus of elasticity of 10% sandblasted concrete is 22531,964 MPa. From the results of the study it was concluded that the use of sandblasting as a substitute for fine aggregate showed an increase in the value of sandblasting variations of 10% for the compressive strength test, split tensile strength test, flexural strength and modulus of elasticity test of concrete.